Real‐time Conversion of Electrochemical Currents into Fluorescence Signals Using 8‐Hydroxypyrene‐1, 3, 6‐trisulfonic Acid (HPTS) and Amplex Red as Fluorogenic Reporters. Issue 12 (18th June 2021) - Djoumer, Rabia; Chovin, Arnaud; Demaille, Christophe; Dejous, Corinne; Hallil, Hamida
Abstract: This paper elaborates on an instrumental scheme for translating electrochemical reactions occurring at an electrode under potentiostatic control into fluorescent signals. We examine the performance enhancement of this device using recently introduced water‐soluble fluorescent reporter systems, either the pH‐sensitive 8‐hydroxypyrene‐1, 3, 6‐trisulfonic acid (HPTS) system or the electrofluorogenic Amplex Red species. The conversion of stationary and transient, cathodic and anodic electrochemical currents into fluorescence is demonstrated. We show that pure capacitive currents can also be converted to fluorescence by our setup, highlighting the rarely observed coupling between a faradaic reaction at one electrode and capacitive charging at another. Abstract : A universal potentiostatic platform for converting oxidative, reductive, and even charging currents into fluorescence is described. The performance improvements and limitations brought by using 8‐hydroxypyrene‐1, 3, 6‐trisulfonic acid (HPTS) and Amplex Red as fluorogenic reporters are evidenced. A seldom reported coupling between a faradaic reaction and a capacitive charging process is directly visualized.